Riesgos del devenir indígena en la migración desde Bolivia a Buenos Aires : identidad, etnicidad y desigualdad - Sergio Caggiano (Les Cahiers ALHIM)
This article aims to highlight the importance of Aymara migration from Bolivia to Buenos Aires and Greater Buenos Aires, in Argentina. It is not concerned with the variety of methodological and theoretical approaches that have oriented studies about this topic, rather it seeks to shed light upon this new phenomenon. The novelty of Aymara migration to Buenos Aires does not lie in the fact that it began recently, rather in indigenous becoming, in the processes of ethnicization and identity formation among a significant portion of these migrants.